In memoriam: Yevgeniy F. Kopeika (October 03rd, 1939 – May 08th, 2018) - Problems of Cryobiology and Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(2): 191